LEGAL ANALYSIS OF THE DISCLAIMER CLAUSE IN THE TOKOPEDIA E-COMMERCE AGREEMENT AND ITS LEGAL IMPLICATIONS BASED ON THE CIVIL CODE - Roosdiana Harahap; Sawitri Yuli Hartati S.; Dewi Nadya Maharani; Hartutik Hartutik; Muhammad Sofwan Taufiq; Savira Puspa Anugrah (Multidisciplinary Research Studies in Social Sciences, 2026)
Advances in digital technology have driven significant changes in economic activity, particularly in the buying and selling practices through e-commerce platforms. Tokopedia, as one of the largest platforms in Indonesia, acts as an intermediary between sellers and buyers without being directly bound by a sales contract. In practice, business actors often include disclaimer clauses unilaterally in electronic agreements to limit or transfer legal responsibility. Such clauses may conflict with basic contractual principles, particularly the principle of freedom of contract, which must be applied in conjunction with the principle of good faith as stipulated in Article 1338 of the Civil Code. This study aims to examine the relationship between the fulfillment of the good-faith element in contracts and the validity of disclaimer clauses, and to provide recommendations for reformulating clauses to align with the principles of justice and consumer legal protection. The method used is normative juridical research, employing a statutory and doctrinal approach by reviewing legal principles, contract theory, and relevant regulations. The research results show that Tokopedia's disclaimer clauses tend to contain unilateral transfers of responsibility without any mechanism for agreement or negotiation, potentially violating the principle of contractual fairness. Therefore, electronic agreement clauses need to be reformulated better to reflect the balance of the parties' positions, uphold the principle of good faith, and provide adequate legal protection for service users.Keywords: Disclaimer Clause, Agreement, e-commerce, Tokopedia, Civil Code